2016
DOI: 10.1016/j.celrep.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

EMRE Is a Matrix Ca 2+ Sensor that Governs Gatekeeping of the Mitochondrial Ca 2+ Uniporter

Abstract: SUMMARY The mitochondrial uniporter (MCU) is an ion channel that mediates Ca2+ uptake into the matrix to regulate metabolism, cell death and cytoplasmic Ca2+ signaling. Matrix Ca2+ concentration is similar to that in cytoplasm, despite an enormous driving force for entry, but the mechanisms that prevent mitochondrial Ca2+ overload are unclear. Here, we show that MCU channel activity is governed by matrix Ca2+ concentration through EMRE. Deletion or charge neutralization of its matrix-localized acidic carboxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 31 publications
4
157
4
1
Order By: Relevance
“…It is possible that NCLX-mediated Ca 2+ -extrusion can compensate for uninhibited influx through MCU, or that MCU is inhibited by elevated [Ca 2+ ] m , limiting Ca 2+ uptake. Indeed, [Ca 2+ ] m regulates MCU Ca 2+ currents with a biphasic [Ca 2+ ] m dependence, with a peak-inhibition [Ca 2+ ] m at ~400 nM (Vais et al, 2016), similar to the resting [Ca 2+ ] m measured here in MICU1_KO cells. Measurements of [Ca 2+ ] m may not reflect total matrix Ca 2+ content.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is possible that NCLX-mediated Ca 2+ -extrusion can compensate for uninhibited influx through MCU, or that MCU is inhibited by elevated [Ca 2+ ] m , limiting Ca 2+ uptake. Indeed, [Ca 2+ ] m regulates MCU Ca 2+ currents with a biphasic [Ca 2+ ] m dependence, with a peak-inhibition [Ca 2+ ] m at ~400 nM (Vais et al, 2016), similar to the resting [Ca 2+ ] m measured here in MICU1_KO cells. Measurements of [Ca 2+ ] m may not reflect total matrix Ca 2+ content.…”
Section: Discussionsupporting
confidence: 72%
“…Since mutation of EF hands did not affect hetero-dimer formation or association with MCU, MICU2 tunes the MICU1-mediated threshold for activation through distinct Ca 2+ -binding properties of MICU1 homo- vs. hetero-dimers. We previously observed loss of gatekeeping in cells with MICU2 deleted (Vais et al, 2016). However, those measurements used a low-affinity Ca 2+ indicator (Fura-2FF; K D = 5.5 μM) that provided inaccurate measurements below 1 μM.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, previous studies indicate that MCU is strongly regulated by Ca 2+ rise in the mitochondrial matrix [39][40][41]. We therefore reasoned that the profound inhibition of cytosolic Ca 2+ signals observed following the knockdown of NCLX is linked to the inhibition of MCU.…”
Section: Mcu Modulates Mitochondrial and Cytosolic Ca 2+ Transientsmentioning
confidence: 92%
“…Previous studies have indicated that a sustained elevation of Ca 2+ concentration in the mitochondrial matrix strongly inhibits Ca 2+ influx through the mitochondrial Ca 2+ uniporter [39,40]. Recent studies show that such regulation is mediated by the interaction of MCU and EMRE [41]. Such a mechanism is required for preventing mitochondrial Ca 2+ overload and also attenuates mitochondrial Ca 2+ shuttling.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The subsequent rise in [Ca 2þ ] i in the apical (secretory) region, where the IP 3 receptors are localized, causes immediate uptake of Ca 2þ into the peri-granular mitochondria via the mitochondrial Ca 2þ uniporter in the inner mitochondrial membrane. Recent work suggests that the gating of this pathway is controlled by a Ca 2þ sensor in the mitochondrial matrix [28]. The rise in the intra-mitochondrial [Ca 2þ ] i , in turn, activates the three Ca 2þ -sensitive dehydrogenases in the Krebs cycle, stimulating ATP production [26].…”
Section: Roles Of Intracellular Ca 2þ and Atp In The Control Of Exocymentioning
confidence: 99%